2008
DOI: 10.3201/eid1405.071398
|View full text |Cite
|
Sign up to set email alerts
|

Extensively Drug-Resistant Tuberculosis,Taiwan

Abstract: Extensively Drug-Resistant Tuberculosis, Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 5 publications
0
28
2
Order By: Relevance
“…Two reasons might contribute to capreomycin and amikacin, in addition to resistance to isoniazid and rifamplicin, as well as ofloxacin. This is significantly higher than the percentages from other studies [21,28]. In China, the above seven drugs are the most commonly used ones to treat TB and DR-TB.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Two reasons might contribute to capreomycin and amikacin, in addition to resistance to isoniazid and rifamplicin, as well as ofloxacin. This is significantly higher than the percentages from other studies [21,28]. In China, the above seven drugs are the most commonly used ones to treat TB and DR-TB.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, the proportion of all MDR-TB patients with cultures resistant to ofloxacin was up to 69.3% in all MDR-TB patients, and the drug resistant proportion of ofloxacin was 56.8% in Other MDR groups, higher than 6.4%, 16.6% and 42.8% which were respectively reported from Latvia [27], South Korea [10] and Tai Wan [28]. Two reasons might contribute to capreomycin and amikacin, in addition to resistance to isoniazid and rifamplicin, as well as ofloxacin.…”
Section: Discussionmentioning
confidence: 75%
“…The median number of drugs to which Mycobacterium tuberculosis isolates were resistant was four (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). A median of six anti-TB drugs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) were used for a median of 27 (1-136) months. Among the patients, 42 (21.3%) had XDR-TB.…”
Section: Demographic Characteristics and Treatment Outcomesmentioning
confidence: 99%
“…Among XDR-TB patients with HIV infection, an alarmingly high fatality rate of nearly 100%, with a median survival of only 16 days, was reported [4]. However, XDR-TB has been reported not only among HIV-infected populations, but also among non-HIV-infected patients [5,6]. The current authors recently examined 211 MDR-TB patients without HIV infection in South Korea and reported that the presence of XDR-TB posed 4.46 times higher odds of treatment failure [7].…”
mentioning
confidence: 99%
“…Recently, an outbreak of extensively drugresistant tuberculosis (XDR-TB) was reported in KwaZulu Natal Province in South Africa, and it had a high mortality rate (98z) (4). Untreatable XDR-TB cases have been reported elsewhere, but rarely in Taiwan (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%